+0  
 
0
238
1
avatar

Attempt to derive the formula for the sum of two cubes. (Proof)

Guest Sep 16, 2017
 #1
avatar+87294 
+2

 

Note

 

(a + b)^3   =  a^3  + 3a^2b + 3ab^2 + b^3

 

(a + b) ^3  = a^3 + 3ab (a + b) + b^3 

 

(a + b) ^3   -   3ab (a + b)  =  a^3  + b^3

 

(a + b)  [( a + b)^2 - 3ab ]  = a^3 + b^3

 

(a + b) ( a^2 + 2ab + b^2 - 3ab)  = a^3 + b^3

 

(a + b) ( a^2 - ab + b^2 )  = a^3 + b^3

 

 

cool cool cool

CPhill  Sep 16, 2017

8 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.